Sulfur-carbon composite material and preparation method thereof
By adsorbing an aqueous hydrogen sulfide solution in the pores of the carbon powder and using hydrogen sulfide peroxide to prepare sulfur-carbon composite materials, the problems of high energy consumption, complex process and poor product consistency in the prior art are solved, and a safe, controllable and low energy consumption are achieved.
Patent Information
- Application Number
- CN202510116460.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-24
- Publication Date
- 2025-03-04
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing methods for preparing sulfur-carbon composite materials have problems such as high energy consumption, large risk coefficient, complex process and poor product consistency.
The aqueous hydrogen sulfide solution is adsorbed through the pores of the carbon powder, and hydrogen sulfide is oxidized into sulfur elemental and water using hydrogen peroxide. The sulfur is deposited in the pores of carbon, and then dried to form a sulfur-carbon composite material.
The preparation of sulfur-carbon composite materials with easy reaction, controllable sulfur deposition, single product, good product consistency, safe and reliable, and low energy consumption is achieved.
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of composite materials, and in particular to a sulfur-carbon composite material and a preparation method thereof. Background Art
[0002] Sulfur-carbon composites are composed of two elements, carbon and sulfur. This material combines the advantages of carbon and sulfur and exhibits unique properties. First, sulfur-carbon composites have high electrical conductivity, thermal conductivity, low density, excellent mechanical properties, good chemical stability and corrosion resistance, making them widely used in electronic devices and heat dissipation systems, aerospace, automobile manufacturing and other fields. Secondly, sulfur-carbon composites have significant application advantages in the energy field, such as lithium-ion batteries, solar cells, and fuel cells. Sulfur-carbon composites can also be used for sewage treatment, which can effectively remove heavy metal ions and organic pollutants in wastewater. As a catalyst carrier, sulfur-carbon composites can also promote the conversion and degradation of harmful substances in exhaust gas. As a new type of composite material, sulfur-carbon composites are gradually becoming a research hotspot in the field of materials science due to their excellent performance and wide application fields. At present, the preparation of sulfur-carbon composites is mainly through the high-temperature decomposition of hydrogen sulfide to deposit sulfur in carbon pores, or heating a mixture of carbon and sulfur to melt sulfur and be adsorbed by carbon. These methods have the problems of high energy consumption, high risk factor, complex process and relatively poor product consistency. Summary of the invention
[0003] The technical problem to be solved by the present invention is: to overcome the shortcomings of the prior art, to provide a sulfur-carbon composite material and a preparation method thereof, to adsorb an aqueous hydrogen sulfide solution through the pores of carbon powder, and to use hydrogen peroxide to oxidize the hydrogen sulfide into elemental sulfur and water, and to deposit sulfur in the pores of the carbon. After drying, a sulfur-carbon composite material is formed, the reaction is easy to occur, the amount of sulfur deposition is controllable, the product is single and the product has good consistency, is safe and reliable, and has low energy consumption.
[0004] The technical solution of the present invention is: In one aspect, the present invention provides a method for preparing a sulfur-carbon composite material, comprising the following steps: S1 Add hydrogen sulfide aqueous solution to the reactor containing carbon powder at 5-25°C, stir while adding, and then let it stand for 20-40 minutes; the volume ratio of hydrogen sulfide aqueous solution to the total pore volume of carbon powder is (0.9-0.95):1, where the pore volume of carbon powder is V g (cm 3 / g), weight is m (g), then the total pore volume of carbon powder V = V g ×m(cm 3 ); S2 adds aqueous hydrogen peroxide solution, stirring while adding, and then allows to stand; S3 is dried at 70-95°C for 60-180min to obtain a sulfur-carbon composite material. When the drying temperature is too low or the drying time is too short, the drying speed is too slow, affecting the drying effect and insufficient water volatilization; while when the drying temperature is too high, the water will boil, and the violent water vapor will discharge the sulfur element from the carbon pores, affecting the overall performance of the sulfur-carbon composite material.
[0005] Among them, the reactor is the place for preparing sulfur-carbon composite materials. The material is required to be resistant to corrosion by aqueous hydrogen sulfide solution and aqueous hydrogen peroxide solution, and PTFE, glass and other materials can be used.
[0006] Preferably, in step S1, the pore size of the carbon powder is 4-100 nm, and the pore volume is 0.5-1.5 cm 3 / g. When the pore size of carbon powder is small, sulfur is mainly deposited on the surface of carbon powder; when the pore size is large, sulfur is mainly deposited in the pores of carbon powder; when the pore size is too large, the carbon skeleton has a poor binding effect on sulfur, and sulfur and carbon are easily separated during use, resulting in a decrease in overall performance.
[0007] Preferably, the concentration of the hydrogen sulfide aqueous solution is 0.2-0.39wt.%, and the concentration of the hydrogen peroxide aqueous solution is 4-8wt.%. The total sulfur deposition amount can be fine-tuned by using a low concentration of hydrogen sulfide aqueous solution, but too low a concentration will result in too low a single sulfur deposition amount, affecting the time to reach the target deposition amount. Too low a concentration of hydrogen peroxide aqueous solution will introduce too much moisture, resulting in a long subsequent drying time; while too high a concentration will present certain safety hazards.
[0008] Preferably, in step S2, the ratio of the volume of the aqueous hydrogen peroxide solution to the total pore volume of the carbon powder is (0.05-0.1): 1. Adding too little aqueous hydrogen peroxide solution will result in incomplete reaction, and hydrogen sulfide will exist in the solution. When drying, the hydrogen sulfide will volatilize, polluting the environment and endangering the safety and health of operators.
[0009] Preferably, in step S2, the standing time is 10-30 min.
[0010] Preferably, the obtained sulfur-carbon composite material is used to replace the carbon powder in step S1, and steps S1-S3 are repeated multiple times to increase the amount of sulfur deposition, thereby obtaining a sulfur-carbon composite material with multiple sulfur depositions.
[0011] On the other hand, the present invention provides a sulfur-carbon composite material prepared by the above-mentioned method for preparing the sulfur-carbon composite material.
[0012] Compared with the prior art, the present invention has the following beneficial effects: The present invention absorbs hydrogen sulfide aqueous solution through the pores of carbon powder, and uses hydrogen peroxide to oxidize hydrogen sulfide into sulfur element and water, and sulfur is deposited in the pores of carbon, and a sulfur-carbon composite material is formed after drying. The present invention adopts an oxidation-reduction reaction in an aqueous solution to prepare a sulfur-carbon composite material, and the reaction proceeds spontaneously at low temperature, thereby avoiding the problems of high energy consumption and complex process, and because the uniformity of the aqueous solution is good, the prepared product has high consistency, and has the advantages of easy reaction, controllable sulfur deposition amount, single product and good product consistency, safety and reliability, low energy consumption, etc. DETAILED DESCRIPTION
[0013] In order to enable persons skilled in the art to better understand the technical solution of the present invention, the technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention.
[0014] The present invention assembles the sulfur-carbon composite materials prepared in the following examples and comparative examples into a CR2032 button-type lithium-sulfur battery, and uses a 0.1C charge and discharge current and a 2-2.5V voltage range to test the cycle performance of the button-type lithium-sulfur battery. The diameter of the positive electrode sheet is 15 mm, the positive electrode current collector is 10 μm copper foil, and the surface density of the positive electrode coating is 4 mg / cm 2 The positive electrode formula is 90wt.% sulfur-carbon composite material, 5wt.% conductive agent SP and 5wt.% binder LA133; a 25μm thick PP / PE composite diaphragm with a diaphragm diameter of 19mm is selected; the electrolyte is MJS-Lis-180101, and the electrolyte addition amount is 40mg; the negative electrode is a lithium sheet with a thickness of 0.5mm and a diameter of 16.5mm.
[0015] Example 1 The preparation method of the sulfur-carbon composite material of this embodiment comprises the following steps: S1 Place a 10mL beaker in a glove box as a reactor. The temperature in the glove box is 5°C. Weigh 1g of CMK-3 carbon powder and place it at the bottom of the beaker. The pore size of the CMK-3 carbon powder is 4nm and the pore volume is 1.5cm 3 / g; use a micro syringe to measure 1.35mL of 0.39wt.% hydrogen sulfide aqueous solution, drop it into the beaker, stir the carbon powder with a glass rod while adding, and let it stand for 20 minutes after adding the hydrogen sulfide aqueous solution; S2 Use a micro syringe to measure 0.132 mL of 4 wt.% hydrogen peroxide aqueous solution and add it dropwise to the beaker, stirring the carbon powder with a glass rod while adding. After the addition is completed, let it stand for 10 minutes; S3, taking out the beaker from the glove box, putting it into a forced air drying oven, and drying it at 70° C. for 180 min to obtain a sulfur-carbon composite material; S4: replacing the carbon powder in step S1 with the obtained sulfur-carbon composite material, and repeating steps S1-S3 until the sulfur content of the prepared sulfur-carbon composite material is detected to be 50 wt.% by an inductively coupled plasma atomic emission spectrometer (ICP-OES).
[0016] Three CR2032 button-type lithium-sulfur batteries were assembled and tested. The initial discharge capacities were 3.188mAh, 3.186mAh, and 3.190mAh, respectively. After 50 cycles, the capacity retention rates were 71%, 71.2%, and 70.9%, respectively.
[0017] Example 2 The preparation method of the sulfur-carbon composite material of this embodiment comprises the following steps: S1 Place a 10 mL beaker in a glove box as a reactor. The temperature in the glove box is 15 °C. Weigh 1 g of XFP10 carbon powder and place it at the bottom of the beaker. The pore size of the XFP10 carbon powder is 50 nm and the pore volume is 0.85 cm 3 / g; use a micro syringe to measure 0.8mL of 0.3wt.% hydrogen sulfide aqueous solution, drop it into the beaker, stir the carbon powder with a glass rod while adding, and let it stand for 40 minutes after adding the hydrogen sulfide aqueous solution; S2 Use a micro syringe to measure 0.045 mL of 8 wt.% hydrogen peroxide aqueous solution and add it dropwise to the beaker. Stir the carbon powder with a glass rod while adding. After the addition is completed, let it stand for 30 minutes. S3, taking out the beaker from the glove box, putting it into a forced air drying oven, and drying it at 90° C. for 60 min to obtain a sulfur-carbon composite material; S4: replacing the carbon powder in step S1 with the obtained sulfur-carbon composite material, and repeating steps S1-S3 until the sulfur content of the prepared sulfur-carbon composite material is detected to be 45 wt.% by an inductively coupled plasma atomic emission spectrometer (ICP-OES).
[0018] Three CR2032 button-type lithium-sulfur batteries were assembled and tested. The initial discharge capacities were 2.871mAh, 2.866mAh, and 2.873mAh, respectively. After 50 cycles, the capacity retention rates were 71.4%, 71.7%, and 71.5%, respectively.
[0019] Example 3 The preparation method of the sulfur-carbon composite material of this embodiment comprises the following steps: S1 Place a 10mL beaker in a glove box as a reactor. The temperature in the glove box is 25°C. Weigh 1g of HPC013 carbon powder and place it at the bottom of the beaker. The pore size of the HPC013 carbon powder is 100nm and the pore volume is 0.5cm 3 / g; use a micro syringe to measure 0.46mL of 0.2wt.% hydrogen sulfide aqueous solution, drop it into the beaker, stir the carbon powder with a glass rod while adding, and let it stand for 30 minutes after adding the hydrogen sulfide aqueous solution; S2 Use a micro syringe to measure 0.05 mL of 6 wt.% hydrogen peroxide solution and add it dropwise to the beaker. Stir the carbon powder with a glass rod while adding. After the addition is complete, let it stand for 20 minutes. S3, taking out the beaker from the glove box, putting it into a forced air drying oven, and drying it at 95° C. for 120 min to obtain a sulfur-carbon composite material; S4: replacing the carbon powder in step S1 with the obtained sulfur-carbon composite material, and repeating steps S1-S3 until the sulfur content of the prepared sulfur-carbon composite material is detected to be 35 wt.% by an inductively coupled plasma atomic emission spectrometer (ICP-OES).
[0020] Three CR2032 button-type lithium-sulfur batteries were assembled and tested. The initial discharge capacities were 2.240mAh, 2.234mAh, and 2.238mAh, respectively. After 50 cycles, the capacity retention rates were 71.9%, 71.8%, and 71.8%, respectively.
[0021] It can be seen from the initial discharge capacity and the capacity retention rate after 50 cycles of Examples 1-3 that the sulfur-carbon composite material prepared in the present invention has good consistency.
[0022] Comparative Example 1 The difference from Example 1 is that in step S1, the temperature in the glove box is 0°C.
[0023] Three CR2032 button-type lithium-sulfur batteries were assembled and tested. The initial discharge capacities were 3.185mAh, 3.187mAh, and 3.180mAh, respectively. After 50 cycles, the capacity retention rates were 69.5%, 70.2%, and 69.3%, respectively.
[0024] By comparing the first discharge capacity and the capacity retention rate after 50 cycles of Example 1 and Comparative Example 1, it can be seen that if the temperature in the glove box is too low, the capacity retention rate will decrease. This is because if the temperature is too low, the viscosity of the hydrogen sulfide aqueous solution will increase, which is not conducive to the full adsorption of the carbon on it. The hydrogen sulfide aqueous solution is more retained on the carbon surface. After oxidation by the hydrogen peroxide aqueous solution, more sulfur is generated on the carbon surface. During the cycle, the carbon has no binding effect on the sulfur on its surface, and it is easy to form a polysulfide shuttle effect, thereby reducing the capacity retention rate.
[0025] Comparative Example 2 The preparation method of the sulfur-carbon composite material of Comparative Example 2 comprises the following steps: S1 Place a 10mL beaker in a glove box as a reactor. The temperature in the glove box is 35°C. Weigh 1g of CMK-3 carbon powder and place it at the bottom of the beaker. The pore size of the CMK-3 carbon powder is 4nm and the pore volume is 1.5cm 3 / g; use a micro syringe to measure 1.35mL of 0.39wt.% hydrogen sulfide aqueous solution, drop it into the beaker, stir the carbon powder with a glass rod while adding, and let it stand for 20 minutes after adding the hydrogen sulfide aqueous solution; S2 Use a micro syringe to measure 0.132 mL of 4 wt.% hydrogen peroxide aqueous solution and add it dropwise to the beaker, stirring the carbon powder with a glass rod while adding. After the addition is completed, let it stand for 10 minutes; S3, taking out the beaker from the glove box, putting it into a forced air drying oven, and drying it at 70° C. for 180 min to obtain a sulfur-carbon composite material; S4: replacing the carbon powder in step S1 with the obtained sulfur-carbon composite material, and repeating steps S1-S3, the number of repetitions being the same as that in embodiment 1.
[0026] Three CR2032 button-type lithium-sulfur batteries were assembled and tested. The initial discharge capacities were 3.056mAh, 3.052mAh, and 3.058mAh, respectively. After 50 cycles, the capacity retention rates were 70.8%, 70.9%, and 71.1%, respectively.
[0027] By comparing the first discharge capacity and the capacity retention rate after 50 cycles of Example 1 and Comparative Example 2, it can be seen that too high a temperature in the glove box will reduce the first discharge capacity. This is because too high a temperature will cause the hydrogen sulfide in the hydrogen sulfide aqueous solution to volatilize, thereby reducing the sulfur content in the hydrogen sulfide aqueous solution. The reduced sulfur content leads to a reduction in the first discharge capacity of the electrode.
[0028] Comparative Example 3 The preparation method of the sulfur-carbon composite material of Comparative Example 3 comprises the following steps: S1 Place a 10mL beaker in a glove box as a reactor. The temperature in the glove box is 5°C. Weigh 1g of CMK-3 carbon powder and place it at the bottom of the beaker. The pore size of the CMK-3 carbon powder is 4nm and the pore volume is 1.5cm 3 / g; use a micro syringe to measure 1.35mL of 0.39wt.% hydrogen sulfide aqueous solution, drop it into the beaker, stir the carbon powder with a glass rod while adding, and let it stand for 50min after adding the hydrogen sulfide aqueous solution; S2 Use a micro syringe to measure 0.132 mL of 4 wt.% hydrogen peroxide aqueous solution and add it dropwise to the beaker, stirring the carbon powder with a glass rod while adding. After the addition is completed, let it stand for 10 minutes; S3, taking out the beaker from the glove box, putting it into a forced air drying oven, and drying it at 70° C. for 180 min to obtain a sulfur-carbon composite material; S4: replacing the carbon powder in step S1 with the obtained sulfur-carbon composite material, and repeating steps S1-S3, the number of repetitions being the same as that in embodiment 1.
[0029] Three CR2032 button-type lithium-sulfur batteries were assembled and tested. The initial discharge capacities were 3.164mAh, 3.165mAh, and 3.162mAh, respectively. After 50 cycles, the capacity retention rates were 71.1%, 71.3%, and 71%, respectively.
[0030] By comparing the initial discharge capacity and the capacity retention rate after 50 cycles of Example 1 and Comparative Example 3, it can be seen that if the standing time in step S1 is too long, the initial discharge capacity will be reduced. This is because the hydrogen sulfide in the hydrogen sulfide aqueous solution is volatile, and the volatilization amount will not have a significant effect on the product performance within a short standing time. However, if the standing time is too long, the sulfur content in the hydrogen sulfide aqueous solution will be significantly reduced due to the volatilization of hydrogen sulfide, thereby affecting the initial discharge capacity of the electrode.
[0031] Comparative Example 4 The difference from Example 1 is that in step S1, the ratio of the volume of the aqueous hydrogen sulfide solution to the total pore volume of the carbon powder is 1:1.
[0032] Three CR2032 button-type lithium-sulfur batteries were assembled and tested. The initial discharge capacities were 3.186mAh, 3.189mAh, and 3.187mAh, respectively. After 50 cycles, the capacity retention rates were 69.1%, 68.9%, and 68.8%, respectively.
[0033] By comparing the first discharge capacity and the capacity retention rate after 50 cycles of Example 1 and Comparative Example 4, it can be seen that when the ratio of the volume of the hydrogen sulfide aqueous solution to the pore volume of the carbon powder in step S1 is too large, the capacity retention rate will decrease. This is because when the ratio of the volume of the hydrogen sulfide aqueous solution to the pore volume of the carbon powder is too large, the pores in the carbon powder are filled with the hydrogen sulfide aqueous solution at one time, and the hydrogen peroxide aqueous solution as an oxidant cannot enter the pores of the carbon powder. The redox reaction mainly occurs on the carbon surface, resulting in a low sulfur content deposited deep in the pores, which affects the cycle performance.
[0034] Comparative Example 5 The difference from Example 1 is that in step S3, the drying temperature is 105°C.
[0035] Three CR2032 button-type lithium-sulfur batteries were assembled and tested. The initial discharge capacities were 3.182mAh, 3.184mAh, and 3.181mAh, respectively. After 50 cycles, the capacity retention rates were 68.7%, 68.2%, and 68.4%, respectively.
[0036] By comparing the first discharge capacity and the capacity retention rate after 50 cycles of Example 1 and Comparative Example 5, it can be seen that if the drying temperature in step S3 is too high, the capacity retention rate will be reduced. This is because when the drying temperature is too high, the moisture in the pores of the sulfur-carbon composite material will boil violently, and the water vapor will be quickly discharged from the narrow pores, which will bring out the sulfur in the pores and affect the cycle performance.
Claims
1. A method for preparing a sulfur-carbon composite material, characterized in that: The following steps are involved: S1 Add hydrogen sulfide aqueous solution into the reactor containing carbon powder at 5-25°C, stir while adding, and then let stand for 20-40 minutes; the volume ratio of hydrogen sulfide aqueous solution to the total pore volume of carbon powder is (0.9-0.95):1; S2 adds aqueous hydrogen peroxide solution, stirring while adding, and then allows to stand; S3 is dried at 70-95°C for 60-180 min to obtain a sulfur-carbon composite material.
2. The method for preparing the sulfur-carbon composite material according to claim 1, characterized in that: In step S1, the pore size of the carbon powder is 4-100 nm, and the pore volume is 0.5-1.5 cm 3 / g.
3. The method for preparing the sulfur-carbon composite material according to claim 1, characterized in that: The concentration of the aqueous hydrogen sulfide solution is 0.2-0.39 wt.%, and the concentration of the aqueous hydrogen peroxide solution is 4-8 wt.%.
4. The method for preparing the sulfur-carbon composite material according to claim 1, characterized in that: In step S2, the ratio of the volume of the aqueous hydrogen peroxide solution to the total pore volume of the carbon powder is (0.05-0.1):
1.
5. The method for preparing the sulfur-carbon composite material according to claim 1, characterized in that: In step S2, the standing time is 10-30 minutes.
6. The method for preparing the sulfur-carbon composite material according to claim 1, characterized in that: The obtained sulfur-carbon composite material is used to replace the carbon powder in step S1, and steps S1-S3 are repeated multiple times to obtain a sulfur-carbon composite material with multiple sulfur deposition.
7. A sulfur-carbon composite material, characterized in that: The sulfur-carbon composite material is prepared by the preparation method of any one of claims 1 to 6.
Citation Information
Patent Citations
Method for preparing battery using carbon / sulfur composite anode material as anode
CN107910585A
Preparation method of high-purity lithium sulfide
CN117550562A
Synthesis method for cathode material in lithium-sulfur battery
US20170271660A1